Konektivitas Wilayah Terhadap Lokasi Posko Penanggulangan Bencana Banjir di Kecamatan Sayung Kabupaten Demak - Anandi, Trivianto Januar; Ariyani, Indrayati; Hariyanto, Hariyanto (Geo-Image, 2019)
This research was purposed to find out the connectivity of the area to the location of flood prevention post in Sayung Demak. The approach used in this research was descriptive kuantitative approach by data processing method using Geographic Information System. Connectivity can be determined by the number of  edges and vertices, by knowing the connectivity to the flood post location in Sayung Demak, it will be easier to get information which village in Sayung should get more attention from related parties due to its difficult location to get reach. The result of the research is there are 3 evacuation sites, 3 health locations, and 1 public kitchen in Sayung. Then Based on the distance,researcher determine which village is closest to the 3 evacuation posts and health posts that have been provided. Based on the calculation can be seen that the lowest connectivity is generally found in the villages that connected to the evacuation posts located in the Purwosarivillage. As well as health posts, the lowest connectivity are generally found in the villages located in the post in the Purwosari village.